2015
DOI: 10.3390/molecules20034395
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals and Other Characteristics of Croatian Monovarietal Extra Virgin Olive Oils from Oblica, Lastovka and Levantinka Varieties

Abstract: Virgin olive oils from the fruits of Croatian autochthonous varieties Oblica, Lastovka and Levantinka were characterized for the first time. Headspace volatiles were analyzed by HS-SPME/GC-FID/MS. The main volatiles were C6 compounds. The most abundant was (E)-hex-2-enal (62.60%-69.20%). (Z)-Hex-3-enal was not found in Lastovka oil, while Levantinka oil did not contain hexanal. Tocopherols, chlorophylls and carotenoids were determined by HPLC-FL. Levantinka oil was characterized by the highest α-tocopherol lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 35 publications
3
15
0
Order By: Relevance
“…In the present study, hexanal was not found in Aaleh, Limli, and Mekki oil varieties. Similar results were also found by Šarolić et al [24] for Levantinka olive oil, a Croatian variety. This result could be explained by the low amount or lack of activity of the enzyme involved in the generation of hexanal in these varieties.…”
Section: Effect Of Cultivar On the Volatile Compounds In Algerian Evoosupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, hexanal was not found in Aaleh, Limli, and Mekki oil varieties. Similar results were also found by Šarolić et al [24] for Levantinka olive oil, a Croatian variety. This result could be explained by the low amount or lack of activity of the enzyme involved in the generation of hexanal in these varieties.…”
Section: Effect Of Cultivar On the Volatile Compounds In Algerian Evoosupporting
confidence: 90%
“…[19] The most prevalent C6 aldehyde present among five olive varieties was (E)-2-hexenal, with concentrations ranging from 10.74 to 26.51 mg/L (Table 2), this result is in accordance with the literature data obtained from other monovarietal olive oils. In fact, (E)-2-hexenal is the most abundant volatile compound in European, [23][24][25][26][27][28][29] Tunisian, [20,30] and Moroccan [21] olive oils. Surprisingly, EVOO obtained from the variety Ferkani did not contain (E)-2-hexenal (Table 2), whereas the latter was found at relatively low amounts in Aaleh and Abani varieties (2.26 and 0.38 mg/L, respectively).…”
Section: Effect Of Cultivar On the Volatile Compounds In Algerian Evoomentioning
confidence: 99%
“…The olive oil of Söbüaşı variety 36.02 mg/100 g was a significant source of α-tocopherol as compared to other varieties. The highest with literature values made on tocopherol contents of several olive oils 12,16,17 . These differences in tocopherol contents may be change depending on fruit varieties, harvest period, ripening stage of fruits or some enviromental factors.…”
Section: Resultssupporting
confidence: 59%
“…Extra virgin olive oil by its low yield is more expensive than other types of olive oil, but it contains the highest level of polyphenols [ 16 ]. Due to the removal of free fatty acids, extra virgin olive oil has a delicate flavor, aroma, and light color [ 14 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Another interesting feature affecting virgin olive oil properties is filtration.…”
Section: Chemical Composition Of Olive Oilmentioning
confidence: 99%